Infection control practices in Jimma, Ethiopia - Kenzie, Madeline; Safdar, Nasia; Abdissa, Alemseged; Yilma, Daniel; Ibrahim, Shoba; Siraj, Dawd (International Journal of Infection Control, 2019)
Healthcare-associated infections (HAIs) are frequent adverse outcomes of medical care. The HAI burden in low- and middle-income countries is much higher and associated with more severe outcomes. The Systems Engineering Initiative for Patient Safety (SEIPS) model provides a framework that can be used to identify barriers and facilitators of infection control practices and evaluate interactions between structures, processes, and outcomes. A qualitative study was done to evaluate the implementation of effective infection control practices at Jimma University Hospital in Jimma, Ethiopia. Twenty-two semi-structured interviews of hospital employees, selected by convenience sampling, were conducted to assess the five components of SEIPS framework: person, physical environment, tasks, organization and tools. The interviews were transcribed, coded for themes, and analyzed using the software Dedoose (Version 8.0.42 SocioCultural Research Consultants, Los Angeles, CA). Staff overwhelmingly reported a shortage of personal protective equipment (PPE) as a barrier to adequate infection prevention and control (IPC) practices but cited poor supply chain management versus financial resources as the cause. Most interviewees also noted unreliable water availability as an impediment for hand hygiene. Prominent facilitators of effective IPC included a manageable workload, sufficient budget, and positive individual attitude towards improving IPC. The major barriers were identified as an inconsistent and incomplete training program for employees, a lack of IPC policies, and a nurse rotation program that increases unit staff turnover. Interventions designed to address the identified barriers include developing IPC policies and protocols, regularly scheduled IPC training, and establishing an HAI surveillance program to better identify IPC trends and track progress. Innovative interventions are needed to improve IPC practices, such as faculty training on supply chain management and utilization of simple local resources to increase hand washing practices.